Effectiveness of Robot-Assisted Gait Training on Gait and Gross Motor Function in Children with Cerebral Palsy : A Literature Review - Devin Mahendika (Talenta Publisher, 2026)
Background: Cerebral palsy (CP) causes motor impairments in children, including abnormal gait, muscle weakness, spasticity, and poor balance. Robot-assisted gait training (RAGT) provides intensive, repetitive gait practice using wearable exoskeletons or treadmill-based systems to promote neuroplasticity, but its effectiveness remains debated. Objectives: To review recent evidence on RAGT effectiveness in children with CP, comparing wearable and tethered systems and their effects on gait, balance, and gross motor function. Methods: A literature search was conducted in PubMed and Scopus (last 5 years). Experimental studies (including RCTs), observational studies, and reviews on RAGT in pediatric CP were selected and narratively synthesized. Results: Recent trials report that wearable RAGT improves Gross Motor Function Measure (GMFM) scores and balance compared to conventional therapy. In contrast, meta-analyses indicate that tethered treadmill-based RAGT does not significantly improve walking speed or distance over standard therapy. Wearable systems using assist-as-needed control allow adaptive overground gait training with more natural sensory feedback, whereas trajectory-controlled devices impose fixed gait patterns. Conclusion: Wearable RAGT with adaptive assistance appears effective in enhancing walking ability, balance, and gross motor function in children with CP, while tethered systems show limited additional benefit. RAGT should be applied as a complementary intervention with individualized protocols. Further research is needed to evaluate long-term outcomes. Keyword: Assist-as-needed, Cerebral Palsy, Exoskeleton, Robot-Assisted Gait Training, Wearable Exoskeleton Latar Belakang: Menelaah bukti terkini efektivitas RAGT pada anak CP, termasuk perbandingan sistem wearable vs tethered, dampaknya pada pola berjalan, keseimbangan, dan motorik kasar, serta mode kendali (assist-as-needed vs trajectory-controlled) dan intensitas latihan. Tujuan: Menelaah bukti terkini efektivitas RAGT pada anak CP, termasuk perbandingan sistem wearable vs tethered, dampaknya pada pola berjalan, keseimbangan, dan motorik kasar, serta mode kendali (assist-as-needed vs trajectory-controlled) dan intensitas latihan. Metode: Pencarian literatur dilakukan di PubMed dan Scopus (5 tahun terakhir) menggunakan kata kunci RAGT dan CP anak. Studi eksperimental, observasional, dan ulasan yang relevan dipilih dan disintesis secara naratif. Hasil: Studi terbaru menunjukkan RAGT wearable meningkatkan skor GMFM (berdiri/jalan/berlari) dan keseimbangan anak CP lebih signifikan dibanding terapi konvensional. Sebaliknya, meta-analisis RAGT tethered di treadmill menunjukkan tidak ada peningkatan signifikan pada kecepatan atau jarak berjalan dibanding kontrol. Eksoskeleton wearable assist-as-needed memberikan latihan berjalan adaptif dengan umpan balik sensorik fisiologis, sedangkan sistem trajectory-controlled memaksakan pola berjalan kaku. Simpulan: Bukti mendukung bahwa RAGT wearable efektif meningkatkan fungsi berjalan, keseimbangan, dan motorik kasar anak CP, dengan kontrol assist-as-needed sebagai faktor kunci. RAGT tethered belum terbukti lebih unggul dari terapi konvensional. Penggunaan RAGT direkomendasikan sebagai pelengkap terapi konvensional dengan protokol latihan terpersonalisasi. Penelitian lanjutan diperlukan untuk mengevaluasi efek jangka panjang dan optimasi desain eksoskeleton bagi anak CP. Keyword: Anak Cerebral Palsy, Eksoskeleton, Intensitas Latihan, Latihan Berjalan, Rehabilitasi Robotik